Biologic therapy for Behçet's uveitis: a systematic review. Issue 8 (1st November 2019) - Uke, Perpetual; Gorodkin, Rachel; Beare, Nicholas
Abstract : Background: Biologics are increasingly used in management of Behçet's Disease (BD) including ocular BD, but the evidence base is limited, mostly from studies of uveitis and BD manifestations. Objective: To review the evidence base for biologics in the treatment of ocular BD. Methods: Systematic literature search was made using exploded key words—Behçet's, ocular, biologics in MEDLINE, Cochrane library, Database of Abstracts Reviews and Effects, Clinical Trials.gov, Science Direct and Google Scholar. There was no limitation on region, language or date (Search updated 16th October 2018). Literature retrieval was restricted to randomised controlled trials (RCTs) of biologics. Results: Of 237 papers retrieved, eight met the inclusion criteria. RCTs on interferon alpha 2a (INF-α 2a), adalimumab, secukinumab, gevokizumab, rituximab and daclizumab were retrieved (two for adalimumab and gevokizumab). The outcome measures were not met for secukinumab, daclizumab and gevokizumab. Rituximab and INF-α 2a showed promising preliminary results but sufficiently powered RCTs are needed to provide adequate evidence of efficacy. The RCTs on adalimumab did not evaluate efficacy for BD uveitis specifically, hence are of limited value for this review. Conclusion: Some biologics show promise in treating BD uveitis, but more RCTs are needed for firm conclusions about efficacy. A phase IV study or, registry of adalimumab could provide data on its efficacy in BD uveitis compared to other forms.